Legal Standing of Land Rights Certificate on Eigendom Verponding Land - Hafidz Indra Pratama; Gunawan Djajaputra (Dinasti Research, 2024)
Many disputable incidents related to the ownership of land previously controlled by Western parties continue to occur, where the owner or heir asserts a claim to ownership of the land, even after the enactment of Law Number 5 Year 1960 on Basic Agrarian Principles, as well as the unchanged status of the land over a 20-year period. This research aims to investigate the legal position of land title certificates related to the concept of eigendom verponding land, as well as the legal protection available to holders of certificates declared invalid by Supreme Court Decision Number 109 PK/Pdt/2022. The methodological approach applied is the normative juridical research method. The research findings show that land previously owned by Western parties becomes direct ownership by the state, so that holders of former eigendom verponding land certificates must still be recognized. This conclusion is based on a theoretical analysis of legal norms derived from various hierarchies of laws and regulations that are interrelated and related to each other. Land that was once part of the eigendom verponding system and has now transitioned into direct state ownership, with the issuance of land title certificates, marks a manifestation of the legal protection afforded to individuals who initially held certificates that were later revoked, in accordance with the principle of legal protection. In this context, objections to the issuance of land rights certificates can no longer be raised in court, because essentially, objections to land rights certificates can only be made within five years of the certificate being issued, as stipulated in Article 32 paragraph (2) of Government Regulation Number 24 of 1997.